Currency Traders and Exchange Rate Dynamics: A Survey of the U.S. Market - Yin-Wong Cheung; Menzie D. Chinn (Center for Economic Studies and ifo Institute (CESifo), 2000)
We report findings from a survey of United States foreign exchange traders. Our results indicate that: (i) in recent years electronically-brokered transactions have risen substantially, mostly at the expense of traditional brokers; (ii) the market norm is an important det e rminant of interbank bid-ask spread and the most widely-cited reason for deviating from the conventional bid-ask spread is a thin/hectic market; (iii) half or more of market respondents believe that large players dominate in the dollar-pound and dollar-Swiss franc markets; (iv) technical trading best characterizes about 30% of traders, with this proportion rising from five years ago; (v) news about macroeconomic variables is rapidly incorporated into exchange rates; (vi) the importance of individual macroe c onomic variables shifts over time, although interest rates always appear to be important; (vii) economic fundamentals are perceived to be more important at longer horizons, while short-run deviations from the fundamentals are attributed to excess speculation and institutional customer/hedge fund manipulation; (viii) speculation is generally viewed positively, as enhancing market efficiency and liquidity, even though it exacerbates volatility; (ix) central bank intervention does not appear to have substantial effect, although there is general agreement that it increases volatility, and finally; (x) traders do not view purchasing power parity as a useful concept, even though a significant proportion (40%) believe that it affects exchange rates at horizons of over six months.
Keywords: 330